Does intermarriage pay off? A panel data analysis - Olga Nottmeyer (Institute for the Study of Labor (IZA), 2010)
Taking advantage of the panel structure of the data, the impact of intermarriage on labor market productivity as measured by earnings is examined. Contrarily to previous studies which rely on instrumental variable techniques, selection issues are addressed within a fixed effects framework. The model accounts for short and long term effects as well as general differences between those who intermarry and those who do not. Once unobserved heterogeneity is incorporated, advantageous effects from intermarriage vanish and do not differ from premiums from marriage between immigrants. However, immigrants who eventually intermarry receive greater returns to experience indicating better labor market integration.
Keywords: J1; J12; 330; intermarriage; integration; labor market; migration